ChemInform Abstract: Cobalt Catalyzed sp3 C—H Amination Utilizing Aryl Azides. Issue 9 (February 2016) - Villanueva, Omar; Weldy, Nina Mace; Blakey, Simon B.; MacBeth, Cora E.
Abstract: A dinuclear Co(II) complex is capable of selective C—H amination to form indolines from aryl azides at low catalyst loading.